Pengaruh Model Contextual Teaching and Learning (CTL) Berbantuan Media Ular Tangga Terhadap Penguasaan Konsep Fisika Siswa - Arin Wildani; Agus Budiyono; Zaitun Zaitun (Department of Physics Education, Universitas Mataram, 2021)
This research was conducted with the aim of knowing the effect of applying the CTL learning model assisted by snakes and ladders media on students' conceptual mastery in pesantren-based schools. This research is a quasi-experimental research with research design using pretest-posttest control group design. The population in this study were all students of a pesantren-based school in Pamekasan. while the sample consists of two groups, namely the experimental class and the control class with the sampling technique using random sampling technique. The sample of the experimental class and control class consisted of 40 students. The experimental class was given the CTL model learning treatment with snakes and ladders media while the control class only applied the CTL model. The instrument used in this research is the student's concept mastery test instrument in the form of multiple-choice questions. Data was collected by means of tests and filling out questionnaires. Data analysis was carried out by using the Independent Sample T Test. The results showed that tcount > ttable with a significance of 0.000 or a significance of <0.05, which means that the snake-and-ladder-assisted model has a significant effect on students' conceptual mastery.